Mechanical and thermal properties of chemical vapor infiltration engineered 2D-woven and 3D-braided carbon silicate composites. Issue 9 (November 2015) - Gao, Yantao; Zhou, Haijun; Liu, Min; Ye, Linfeng; Xia, Huihao
Abstract: SiCf /SiC composites reinforced with either two-dimensional woven or three-dimensional braided preforms were fabricated by the chemical vapor infiltration (CVI) process. The microstructure, mechanical and thermal properties of the composites were studied. In comparison, the 3D-braided out-performed 2D-woven composites based on the mechanical and thermal properties. The geometry and microstructure determinants of the properties of the composites were investigated. Additionally, we tested how resilient the SiCf /SiC composites were in contact with eutectic molten salt of LiF, NaF and KF to determine whether such materials could function in a molten salt reactor. The molten salt had minimal influence on mechanical properties of SiCf /SiC composites due to the SiC coating blocking the infiltration of molten salt. Our data demonstrated the feasibility of CVI produced SiCf /SiC composites with potential applications in molten salt reactor.